La importancia del juego en el desarrollo cognitivo de los niños y niñas de 4 a 5 años en el CEI “Teresa León de Noboa” del cantón Guaranda provincia Bolívar en el periodo – noviembre 2022 – marzo - Bonilla Guzmán, Fátima Belén (2023)
In the present investigation that takes as its theme the importance of play in the cognitive development of boys and girls from 4 to 5 years old in the CEI "Teresa León de Noboa" of the Guaranda Canton, Bolívar province in the period 2023, the Play contributes to the cognitive development of boys and girls since it is very important in the first years of life, because that is where they begin to acquire skills and abilities that allow them to achieve adequate learning. The game addresses different problems that are presented in the "Teresa León de Noboa" initial education center due to the lack of use of games in boys and girls, causing difficulties in their academic performance. The present investigation focused on the qualitative-quantitative approach, which allowed us to collect information to immediately analyze and interpret it. The instruments were applied to 16 people, both infants and educators, with the results obtained it was possible to detect the lack of use of the game, since the game is an important tool in the children, the educators spent less time to carry out activities and the little importance they had to the game, where game activities must be carried out from an early age. Carrying out activities that contain the game and positively develop cognitive development within the initial education center; Finally, it was proposed as an alternative solution to apply strategies to develop the cognitive part, improving academic performance in infants, promoting knowledge of the game, allowing the acquisition of skills